Pengaruh Akreditasi Sekolah Terhadap Peningkatan Jumlah Peserta Didik Baru Sma Di Kabupaten Barito Kuala - Marisa .; Suratno .; Melly Agustina Permatasari; Monry Fraick Nicky Gillian Ratumbuysang (CV. ITTC INDONESIA, 2025)
This study aims to analyze the effect of school accreditation on the increase in the number of new high school students in Barito Kuala Regency. The problem raised in this study is how school accreditation influences prospective students' decisions in choosing a school and how much impact it has on the number of new student enrollments. The approach used in this study is quantitative, with data analysis using inductive statistical methods (inferential statistics) and data processing carried out using Microsoft Office Excel software. The type of data used is time series data with an observation period of the last three years from 2022 to 2024. The data used in this study is secondary data obtained by third-party processing, sourced from official publication reports of the Central Statistics Agency (BPS), Dapodikdasmen, School/Field Data, and Literature Studies. The results of the study show that schools with A accreditation consistently have a higher number of new students compared to schools with B and C accreditation. However, schools with B accreditation still show high competitiveness like schools with A accreditation. Meanwhile, schools with C accreditation have a lower number of students, although it remains stable. Accreditation has been proven to influence public perception and serve as a quality indicator that plays a role in parents' and students' school choices. Therefore, improving school quality through accreditation is crucial for increasing school attractiveness and increasing the number of new students.